(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Neem plant (Azadirachta indica), a traditionally known medicinal plant is very effective in various diseases. We are trying to assess the activity of Nimbaflavone, one of the extracts of Neem plant in In silico approaches to understand the role of this extract in inhibition of intermediate molecules associated in the pathway of rheumatoid arthritis. PTPN22 has been found to be linked with the autoimmune diseases including RA, which play significant role in T cell signalling. The established function of PTPN22 in the functioning of CD8 memory T cells and the development of interleukin-17-producing T helper (Th17) cells, which participates in the production of proinflammatory cytokine.